A comparative study of different segments in the South African lending industry - J. Volschenk; N. Biekpe (South African Journal of Business Management, 2003)
The efficiency and availability of financial services for the poor is a global problem, and has only recently started to attract attention in South Africa. This paper aims to examine the South African microfinance industry by comparing sector-related differences in the ranking of specific problems. Tests for the significance of differences (in the location of specific populations) indicate significant differences in perceptions regarding certain intra-industry segments within the microcredit industry. The recent arguments in favour of a single regulator imply that the financial industry as a whole (commercial and microlending sectors) is homogeneous in its priorities. However, the results in this paper suggest that there is no significant agreement between the priorities of the commercial and microlending industries.
Keywords: 650